PENGARUH PENURUNAN MUKA TANAH TERHADAP KEPADATAN PENDUDUK DAN BENCANA BANJIR DI KOTA SEMARANG - Rahman, Muhammad Farras (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
This study investigates the relationship between land subsidence, population density, and flood disasters in Semarang City using a multiple linear regression approach. Data from 2012 to 2022 include land subsidence rates, population density, and flood inundation heights. Classical assumption tests—Breusch-Pagan for heteroskedasticity, Variance Inflation Factor (VIF) for multicollinearity, and Shapiro–Wilk for normality—were applied to ensure model validity. The results indicate that both population density and flood inundation height exert a positive but statistically insignificant effect on land subsidence. The model explains 57.6% of the variation in land subsidence. These findings suggest that future studies should incorporate additional variables, such as groundwater extraction rates and infrastructure development, to enhance model accuracy and provide a more comprehensive understanding of land subsidence dynamics in coastal urban areas.